Rancang Bangun Deteksi Banjir Menggunakan NodeMCU Dengan Notifikasi Berbasis Android Pada Komplek Ciledug Indah 1 - Selvy Pebrianti; Saprudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2023)
Floods are natural disasters that often occur in several areas in Indonesia, one of which is in Jakarta. As in the Ciledug Indah 1 Complex which is adjacent to the river, which often floods due to the large amount of garbage that clogs, the flow of river water often floods at night and at that time residents who are sleeping do not know that the flood has entered the house so that household items been flooded. This researcher aims to produce a flood detection system so that residents know about an impending flood by using messages and voices. This flood warning detection system uses NodeMcu which controls ultrasonic sensors to detect flooding from its height. The message sent by the Android application will send a flood hazard notification depending on the condition of the ultrasonic sensor which detects the height at each predetermined water level, in addition to notification of a buzzer sound that informs the danger sign at the highest level which will sound 1 time later. The result of this research is that an early warning flood detection system has been built using NodeMcu and an Android application that makes it easier for residents to find out the state of overflowing water from rivers near settlements.